2023
DOI: 10.12714/egejfas.40.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anti-cancer and antioxidant properties of protein extracts obtained from aquatic Helophorus (Coleoptera: Helophoridae) insects

Abstract: In this study, protein extraction was performed from the aquatic insect Helophorus aquaticus (Linnaeus, 1758) and Helophorus syriacus (Kuwert, 1885) species belonging to the genus Helophorus (Coleoptera: Helophoridae). Then, these protein extracts were studied in vitro. These species were collected from the shallow parts of various streams, springs, creeks, ponds and hot springs from Bingöl city centre and its districts between May to June 2017. The protein amount was determined 34.78 mg/mL in the H. aquaticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…In vitro studies on the prostate cancer cell line PC-3 indicated the antioxidant and anticancer activities of protein extracts of Helophorus aquaticus and Helophorus syriacus. The protein extracts of both insects showed high efficacy in cell inhibition and produced significant apoptosis at a dose 1,000 μg/mL (Elhazar et al, 2023). Several studies have reported the anti-neoplastic activity of extracts of Periplaneta americana which belongs to order Dictyoptera and family Blattidae (Zhao et al, 2017).…”
Section: Insect Extractsmentioning
confidence: 98%
“…In vitro studies on the prostate cancer cell line PC-3 indicated the antioxidant and anticancer activities of protein extracts of Helophorus aquaticus and Helophorus syriacus. The protein extracts of both insects showed high efficacy in cell inhibition and produced significant apoptosis at a dose 1,000 μg/mL (Elhazar et al, 2023). Several studies have reported the anti-neoplastic activity of extracts of Periplaneta americana which belongs to order Dictyoptera and family Blattidae (Zhao et al, 2017).…”
Section: Insect Extractsmentioning
confidence: 98%